Measurement of neurotic symptoms by self-report questionnaire: validity of the SCL-90R. - Peveler, R; Fairburn, C (1990)
The Symptom Check List (SCL-90R) is a self-report questionnaire which is designed to be suitable for use as a psychiatric case-finding instrument, as a measure of symptom severity, and as a descriptive measure of psychopathology. Scores obtained using the instrument were compared with those obtained from the investigator-based interview, the Present State Examination, in two samples of patients: a sample of patients with chronic physical disease (diabetes mellitus) and a sample of patients with bulimia nervosa. There was good agreement between the two methods of measurement in both samples, suggesting that the SCL-90R performs well in the assessment of neurotic symptoms.